2020
DOI: 10.3390/genes11111334
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Shall We Target CD33?

Abstract: Background: Multiple sclerosis (MS) is a chronic disease of the central nervous system (CNS). Myeloid lineage cells (microglia and macrophages) may participate in the pathogenic mechanisms leading to MS. CD33 is a transmembrane receptor, mainly expressed by myeloid lineage cells. CD33 rs3865444 is a promoter variant previously associated with Alzheimer’s disease, whose role in MS remains obscure. Objective: To assess the role of CD33 rs3865444 in MS risk. Methods: We genotyped 1396 patients with MS and 400 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(43 reference statements)
1
8
1
Order By: Relevance
“…Its genetic background is known to be strong, with numerous susceptibility foci having been identified [11], and more than 110 genetic risk factors of MS have been pinpointed [12,13], though the genetic components alone do not suffice to explain its occurrence, as shown by the fact that homozygotic twins do not present the exact same rates of MS [14]. In fact, the genetic risk loci, alongside major risk HLA variants, can only explain approximately 30% of MS heritability, revealing the strong contribution of environmental factors to MS pathophysiology [15][16][17][18]. In this regard, various environmental factors have been pinpointed as risk factors for MS, such as viral infections [19], and interactions between specific polymorphisms and environmental risk factors have also been documented [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Its genetic background is known to be strong, with numerous susceptibility foci having been identified [11], and more than 110 genetic risk factors of MS have been pinpointed [12,13], though the genetic components alone do not suffice to explain its occurrence, as shown by the fact that homozygotic twins do not present the exact same rates of MS [14]. In fact, the genetic risk loci, alongside major risk HLA variants, can only explain approximately 30% of MS heritability, revealing the strong contribution of environmental factors to MS pathophysiology [15][16][17][18]. In this regard, various environmental factors have been pinpointed as risk factors for MS, such as viral infections [19], and interactions between specific polymorphisms and environmental risk factors have also been documented [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Moving on, MS and IS share several other common elements besides neuroinflammation. Firstly, the genetic background of MS is indisputable [10,84,85]. Recent reports have claimed that MS and IS are also genetically linked [86], with numerous shared genes and similar gene expression levels [87].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, with the loss of CD33 inhibitory activity, CD33 gene could have a role in NMOSD pathogenesis through the regulation of the immune system. In a recent study, Siokas et al [36] have reported that CD33 rs3865444 polymorphism is associated with multiple sclerosis that shares some similarities with NMOSD, and like NMOSD, is an inflammatory disease. The results indicated that CD33 rs3865444 polymorphism could be associated with the risk of multiple sclerosis in the dominant (OR [95% CI] = 0.79 [0.63-0.99], p = 0.041) and overdominant (OR [95% CI] = 0.77 [0.61-0.97], p = 0.03) genetic models.…”
Section: Discussionmentioning
confidence: 99%